Multi Aspect Model Of Sustainable Edu-Tourism Development Based On Kelulut Honey Bee Cultivation (Trigona Spp) In Kubu Raya Regency-West Kalimantan - Hamzah Hamzah; Marhamah Marhamah; Syarif Muhammad Syaifuddin (UNIVED Press, 2025)
The Multi Aspect Sustainability Analysis Model is employed as an analytical framework to evaluate the sustainability of kelulut honeybee cultivation in the context of Edu-Tourism development in Kubu Raya Regency. This comprehensive analysis encompasses several key aspects, including educational concepts, ecological considerations, economic implications, and strategic frameworks for promotion and marketing. The findings from this study indicate that under current conditions, kelulut honeybee cultivation is unsustainable for Edu-Tourism development. However, in Scenario 1, marked by a sustainable status, it emerges as the most favorable alternative for the progressive development of Edu-Tourism in the region. It is crucial to recognize that the development of Edu-Tourism based on kelulut honeybee cultivation requires prioritizing several key aspects: education (1), ecology (2), economy (3), and promotional strategies (4), to significantly enhance sustainability values in the Edu-Tourism development process.